2022
DOI: 10.1111/psj.12480
|View full text |Cite
|
Sign up to set email alerts
|

Shifting narrative strategies: How monument advocates change their stories in response to conflict over time

Abstract: This paper expands the Narrative Policy Framework (NPF) by employing an exploratory case study approach to examine the construction of narratives temporally. A large‐N Twitter dataset concerning the Bears Ears and Grand Staircase‐Escalante monuments controversy is utilized to examine the question: how does the use of narrative strategies change over time? Through the application of change‐point analysis, we determine time points of significant shifts towards use of the devil‐angel shift, scope of the conflict,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…In the next article, "Shifting Narrative Strategies: How Monument Advocates Change Their Stories in Response to Conflict over Time, " Rupinsky et al (2023) extend previous NPF studies by utilizing a case study method to explore how narratives are generated temporally. To answer the question of how narrative strategies evolve over time, the authors used a change-point analysis of a massive Twitter dataset related to the Bears Ears and Grand Staircase-Escalante monuments controversy.…”
Section: Editorial Introduction: Contributing To the Policy Process L...mentioning
confidence: 94%
See 1 more Smart Citation
“…In the next article, "Shifting Narrative Strategies: How Monument Advocates Change Their Stories in Response to Conflict over Time, " Rupinsky et al (2023) extend previous NPF studies by utilizing a case study method to explore how narratives are generated temporally. To answer the question of how narrative strategies evolve over time, the authors used a change-point analysis of a massive Twitter dataset related to the Bears Ears and Grand Staircase-Escalante monuments controversy.…”
Section: Editorial Introduction: Contributing To the Policy Process L...mentioning
confidence: 94%
“…The analysis suggests that there have been significant shifts toward the utilization of the devil‐angel shift , the scope of the conflict , and causal mechanism strategies at various points in time. Rupinsky et al (2023) conclude that organizations remain consistent in their utilization of narrative strategies over the entire course of a policy conflict, only varying them in response to events. Consequently, they recommend refining and expanding NPF hypotheses as well as conducting a more detailed investigation into how narrative strategy use changes according to specific policy events throughout the process.…”
mentioning
confidence: 99%
“…For many aspects, the agenda of this study remains in familiar territories for the NPF (see Schlaufer et al., 2022): it is set in liberal democracy, it focuses on a single (European) country where NPF has been applied (Lyytimäki, 2023; Peltomaa, 2018; Peltomaa et al., 2020); it uses policy documents and media as data sources, and it investigates environmental policy, a field that has been the most popular policy field within NPF scholars up to date (Schlaufer et al., 2022). In recent NPF studies, scholars have shown that the NPF has neither been utilized for its full potential to study the aspects of temporality (Rupinsky et al., 2023), nor does it distinguish the policy substance and process (Kuenzler & Stauffer, 2022), both of which are at the core of strategic policy‐making. Thus, this article tests and develops additions to the framework to better understand the co‐existent, implicit narratives of the future in policy communication.…”
Section: Introductionmentioning
confidence: 99%